Papillon-Leage and psaume syndrome patient with multiple dental and orofacial anomalies - Kılınç, Delal Dara; Özsarp, Ecem (Wolters Kluwer Medknow Publications, 2019)
Papillon-Leage-Psaume Syndrome, also known as oral-facial-digital syndrome (OFDS) type I, describes a group of neurodevelopmental disorders that are characterized by anomalies of the oral cavity, facial features, and the digits. Central nervous system (CNS) anomalies and visceral organ abnormalities such as kidney, pancreas, and ovarian cysts can also be seen in these patients. Among 13 potential types, female-inherited OFDS type I is the most common and it has been reported to be lethal in males. After the identification of the genetic relation of OFDS in 2001, it is now known that, except X-linked OFDS Type I and VIII, generally all types of OFDSs are autosomal recessive. The dentist's knowledge about the syndrome can reduce the development of physical and dental anomalies by facilitating early diagnosis. This article presents a patient with Papillon-Leage-Psaume Syndrome (Oral-Facial-Digital Syndrome Type I).
WOS: 000471973600021
PubMed ID: 31187776
Keywords: Cleft Palate; Oral-Facial-Digital Syndrome Type I; Papillon-Leage Psaume Syndrome